2017
DOI: 10.18203/2320-1770.ijrcog20171975
|View full text |Cite
|
Sign up to set email alerts
|

Current placenta previa management and outcome in a rural tertiary care centre

Abstract: Background: The reported incidence for placenta previa averages 0.3% or 1 case in 300 to 400 deliveries. Multiparity, advanced maternal age, cigarette smoking, previous caesarean delivery, history of abortions or uterine surgical procedures are some of the risk factors contributing to the development of placenta previa. Massive obstetrical haemorrhage in placenta previa is associated with severe maternal morbidity and mortality. A significant number of mothers can be saved if right approach of management is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Regarding demographic data, the present study goes in agreement with Sood et al (8) who reported that, majority of their patients were in the age group 20-35 years and the mean maternal age at development of placenta previa was 27.9±4.4 years. On the other side, Refaie et al (9) and Arduini et al (10) reported a mean maternal age of 33.59 ± 4.46 and 36.5 years respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding demographic data, the present study goes in agreement with Sood et al (8) who reported that, majority of their patients were in the age group 20-35 years and the mean maternal age at development of placenta previa was 27.9±4.4 years. On the other side, Refaie et al (9) and Arduini et al (10) reported a mean maternal age of 33.59 ± 4.46 and 36.5 years respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The present study agrees with Arduini et al (10) as they reported that, the mean gravidity and parity were 2.4 and 1.1 respectively and study done by Refaie et al (9) who found that the mean of gravidity was 4.02 ± 1.35 and the mean of parity was 2.74 ± 0.99. Sood et al (8) found that parity range from 2-4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation